A 1.5 Ma Marine Record of Volcanic Activity and Associated Landslides Offshore Martinique (Lesser Antilles): Sites U1397 and U1399 of IODP 340 Expedition - Villemant, Benoît; Le Friant, Anne; Caron, Benoît; Del Manzo, Giulia; Lafuerza, Sara; Emmanuel, Laurent; Ishizuka, Osamu; Guyard, Hervé; Labourdette, Nathalie; Michel, Agnès; Hidalgo, Samia (Frontiers in Earth Science, 2022)
The products of eruptive and mass-wasting processes that built island arc volcanoes are better preserved in marine deposits than on land. Holes U1397A and U1399A drilled during IODP Expedition 340 provide a 1.5 Ma record of the volcanic history of Martinique. 14C dating and δ18O patterns are used to reconstitute the chronostratigraphy of tephra, volcaniclastic turbidites, and mass-wasting events (traced by debris avalanches, debrites, and duplication and deformation of pre-existing sediments), leading to a new volcanic history of Montagne Pelée and Pitons du Carbet volcanoes. The top 50 m of core U1397A provides a continuous high-resolution sedimentation record over the last ∼130 ka. The sedimentation record deeper than 50 m in core U1397A and in the whole core U1399A is discontinuous because of the numerous sliding and deformation events triggered by debris avalanches related to flank collapses. Three successive activity periods are identified since ∼190 ka: the “Old Pelée” until 50 ka, the “Grand Rivière” (50–20 ka), and the “Recent Pelée” (20 ka—present day). The first two periods have the highest volcanic deposition rates offshore but very little outcrop on land. The whole magmatic activity of Mt Pelée comprises silicic andesites, but mafic andesites were also emitted during the whole “Grand Rivière.” At ∼115 ka, a major flank collapse (“Le Prêcheur”) produced a debris avalanche and submarine landslide that affected sea floor sediments by erosion and deformation up to ∼70 km from the shore. The Pitons du Carbet volcano was active from 1.2 Ma to 260 ka with numerous large flank collapses at a mean rate of 1 event every 100 ka. The average deposition rate of tephra fall offshore is much less than that at Mt Pelée. Our data show that correlations between the timing of large landslides or emission of mafic magmas and rapid sea level rise or lowstands suggested by previous studies are not systematic. The reconstituted chronostratigraphy of cores U1397A and U1399A provides the framework necessary for further studies of the magma petrology and production rates and timing of the mechanisms triggering flank collapses and related submarine landslides of Mt Pelée and Pitons du Carbet.